Chaining Differential Reinforcement of Compliance and Functional Communication Training to Treat Challenging Behavior Maintained by Negative Reinforcement - Emily L. Ferris; Alexandra R. Howard; Eleni Baker; Andrew R. Craig; Henry S. Roane; William E. Sullivan (Behavioral Sciences)
Differential reinforcement of compliance (DRC) and functional communication training (FCT) are two effective treatments for escape-maintained behavior. They each, however, have unique limitations. This study aimed to replicate and extend past work by isolating the effects of each treatment and assessing for treatment preference. FCT produced larger reductions in challenging behavior and lower levels of compliance relative to DRC, which produced elevated levels of both compliance and challenging behavior. Additionally, all participants preferred FCT to DRC. Overall, challenging behavior was low and compliance was high when both treatments were embedded within a chained schedule, and these reductions were maintained throughout fading.